PRODUKSI PENGETAHUAN SEKSUALITAS PELAKU FREE SEX DI KALANGAN MILITER - Pramita, Sonya (Jurnal Mahasiswa Sosiologi, 2013)
Introduction : This study discusses the production of sexuality knowledge of free sex actors in the military. The purpose of the study is to analyze the production of sexuality knowledge of free sex actors in the military and how the knowledge limits the disciplinary body of free sex actors in the military. Benefits of the research are as a study material in the realm of sociology, especially on issues of community development and the production of knowledge about sexuality that has power of his body that cannot be contained within the system of military power. This study uses the Michel Foucault theory to analyze the problem of knowledge production about sexuality that limits the disciplinary body of free sex actors in the military. According to Foucault, body can not be in repression by the knowledge and power that is run through the system in the military. The method that is used in this study is qualitative method using genealogy approach. Method : Genealogy is a method developed by Foucault to see the production of power, where the power is formed by differences in regulation, hierarchy is the form of regulation in military that is produced by knowledge that limits the body of free sex actors through a system of military members. Power production limits the body by producing knowledge formation and then generates power. Result : Results from this study is that the production of sexuality knowledge of free sex actors in the military has its function when the body that supposed to work efficiently and productively in repression by the system through military power which is hierarchical, then it is not compatible with the body's own productivity. When the body produces power mismatch then the body produces other discourse outside the power at that moment. According to Foucault, when the power is in the repression of the body, then the body has his own power that could produce another discourse through which knowledge which is formed from regulation. With the draft of free sex, then it is freeing military personnel to produce its own discourse outside the military system that applies in the legislation. Keywords: Sex, Military, Discourse, Knowledge, and Power